Klasifikasi Citra Virus SARS-COV Menggunakan Deep Learning - Susilawati, Indah; supatman, supatman; Witanti, Arita (Jurnal Informatika: Jurnal Pengembangan IT, 2023)
Various variants of the SARS-COV virus emerged from 2003 to early 2022. This resulted in a heavy burden on the health sector in carrying out its duties and public services. It would be very helpful if a computer-assisted application was available that could distinguish between the variants of the SARS-CoV virus. From a scientific point of view, this is an opportunity for information technology to play its role to classify SARS-COV variants using supporting algorithms, including the use of artificial intelligence. Artificial intelligence-based and computer-assisted processes are certainly more immune to negative effects due to repetitive works and fatigue. In this study, Classification of the SARS-COV Virus Image Using Deep Learning (CNN) was carried out based on microscopic data called Transmission Electron Microscopy (TEM) images. The aim of the research is to produce a neural network (CNN/Deep Learning) that has been trained to classify two types of variants of the SARS virus, namely SARS-COV and SARS-COV2. The research phase includes data collection, data pre-processing (consists of the image format conversion and enhancing process), and the classification stage. The classification is carried out using both of the original and enhanced image data. The highest classification accuracy was obtained when the original image data was used, namely 77.66%. It was also found that the classification accuracy increased with an increase in the input image size, but the image data enhancing process used was not able to increase the classification accuracy beyond the classification accuracy achieved when using the original image.